Graphene oxide-based injectable conductive hydrogel dressing with immunomodulatory for chronic infected diabetic wounds. (December 2022) - Ou, Xiaolan; Guan, Lin; Guo, Wenlai; Zhang, Xi; Wu, Siyu; Guo, Deming; Li, Ruiyan; Zvyagin, Andrei V.; Lin, Quan; Qu, Wenrui
Graphical abstract: The mechanisms of accelerating infected diabetic wound healing of graphene oxide-based injectable conductive hydrogel. Highlights: The hydrogel exhibited excellent self-healing properties, injectability, conductivity, biocompatibility, and antibacterial properties. The synergistic antibacterial effect of chitosan and polymyxin B can effectively control the mixed infection of diabetic wounds. Graphene oxide-based conductive hydrogels can modulate the local immunity of diabetic wounds to accelerate the healing of diabetic wounds. The hydrogel can promote M2 polarization, and improve the local inflammation, and angiogenesis, accelerating the healing of diabetic wounds. Abstract: The main challenges of chronic wounds represented by diabetic wounds are that the infection is not easily controlled and the healing is difficult, mainly due to the high-glucose microenvironment, M1 macrophage aggregation, and persistent inflammation. Previous studies inspired by endogenous electric fields have demonstrated that conductive materials can promote cell proliferation, migration, etc., to promote wound healing. However, no study has been conducted on the effect of conductive materials on local immunity. To this end, this study designed a graphene oxide-based conductive hydrogel to repair infected diabetic wounds. Self-healing injectable conductive hydrogels were synthesized by dynamic Schiff-base reaction and electrostatic interactions between oxidized hyaluronic acid, N -carboxyethyl chitosan, graphene oxide, and polymyxin B. The study found that the hydrogel has good biocompatibility and antibacterial properties. In addition, in vivo experiments confirmed that the hydrogel could modulate macrophage polarization to improve the local inflammatory microenvironment, promote neovascularization, and significantly accelerate the healing of diabetic wounds. Most notably, graphene oxide-based conductive hydrogels can modulate local immunity in diabetic wounds to promote healing. This study provides new guidelines for expanding research on conductive materials and new directions for promoting healing in infected diabetic wounds.